Computational fluid dynamic analysis of truck trailer combination on drag reduction / Mohamad Tajudin Sallehudin - Sallehudin, Mohamad Tajudin (2010)
Aerodynamic forces are important aspects that need to be considered in the study of a road vehicle design. The present study focuses on the effect ofbasic truck trailer, truck trailer with air deflector and tuck trailer with air deflector and air frame at different velocity with reference to drag coefficient. The aim of this project is to compare the aerodynamic characteristics of truck trailer between the 3 different conditions. The method of study that was used in this project is simulation using Computational Fluid Dynamic (CFD), STAR-CCM+ software program. Besides that, the truck model is generated using CATIA V5R16 to create the 3-D geometry of the truck trailer. Drag coefficient was obtained from the simulation processes. This thesis represents extensive discussion of numerical solution and the outcomes from the simulations. Comparison of drag coefficient was made for each model with the different velocity.